2016
DOI: 10.1523/jneurosci.4394-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Alcohol-Induced Dysregulation in Dopamine Network Dynamics May Rescue Maladaptive Decision-making

Abstract: Alcohol is the most commonly abused substance among adolescents, promoting the development of substance use disorders and compromised decision-making in adulthood. We have previously demonstrated, with a preclinical model in rodents, that adolescent alcohol use results in adult risk-taking behavior that positively correlates with phasic dopamine transmission in response to risky options, but the underlying mechanisms remain unknown. Here, we show that adolescent alcohol use may produce maladaptive decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 48 publications
(31 reference statements)
8
43
0
Order By: Relevance
“…In agreement with this, another study found adolescent alcohol exposure enhances VTA-stimulated dopamine release in the NAc, and an ethanol challenge produces larger increases in stimulated dopamine release compared with alcohol-naive animals (Shnitko et al, 2016). Interestingly, the administration of an allosteric GABA A agonist attenuates both increased dopamine release and increased risk-taking behavior in animals with adolescent alcohol exposure (Schindler et al, 2016). These findings suggest that there is increased inhibitory tone after alcohol exposure that drives changes in dopaminergic signaling through a disinhibitory mechanism, which may contribute to the behavioral changes.…”
Section: Adaptations In Catecholamine Functionsupporting
confidence: 52%
See 3 more Smart Citations
“…In agreement with this, another study found adolescent alcohol exposure enhances VTA-stimulated dopamine release in the NAc, and an ethanol challenge produces larger increases in stimulated dopamine release compared with alcohol-naive animals (Shnitko et al, 2016). Interestingly, the administration of an allosteric GABA A agonist attenuates both increased dopamine release and increased risk-taking behavior in animals with adolescent alcohol exposure (Schindler et al, 2016). These findings suggest that there is increased inhibitory tone after alcohol exposure that drives changes in dopaminergic signaling through a disinhibitory mechanism, which may contribute to the behavioral changes.…”
Section: Adaptations In Catecholamine Functionsupporting
confidence: 52%
“…Release magnitudes are likewise suppressed in the medial PFC when ethanol is infused directly into the VTA , and a systemic ethanol challenge also reduces NAc dopamine release (Shnitko et al, 2016). In animals with adolescent alcohol exposure, tonic levels of NAc dopamine are reduced in adulthood, and these animals exhibit increased risk-taking behavior (Schindler et al, 2016). Although tonic NAc dopamine is reduced, phasic NAc dopamine release is increased in animals with adolescent alcohol exposure, in a manner dependent on stimulation location: PPTg-but not MFB-evoked phasic dopamine release is increased compared with alcoholnaive animals (Schindler et al, 2016).…”
Section: Adaptations In Catecholamine Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic intermittent exposure to ethanol or training with an alcoholic food reward both separately enhance dopamine release to a Pavlovian CS, though combining these manipulations has no effect in comparison to controls (Fiorenza et al, 2018). Adolescent alcohol exposure has also been shown to enhance dopamine release to Pavlovian cues (Schindler et al, 2016). We are not aware of any previous investigations of ethanol effects on VP cue encoding, though ethanol injections into the ventral tegmental area have been shown to increase extracellular dopamine levels in VP (Ding et al, 2011), and systemic ethanol decreases levels of extracellular GABA in VP (Kemppainen et al, 2010).…”
Section: Disruptions Of Cue Learning or Encoding By Alcohol Exposurementioning
confidence: 99%